2020
DOI: 10.1111/1751-7915.13550
|View full text |Cite
|
Sign up to set email alerts
|

One‐carbon metabolism, folate, zinc and translation

Abstract: The translation process, central to life, is tightly connected to the one-carbon (1-C) metabolism via a plethora of macromolecule modifications and specific effectors. Using manual genome annotations and putting together a variety of experimental studies, we explore here the possible reasons of this critical interaction, likely to have originated during the earliest steps of the birth of the first cells.Methionine, S-adenosylmethionine and tetrahydrofolate dominate this interaction. Yet, 1-C metabolism is unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 245 publications
1
21
0
Order By: Relevance
“…What if one of the overlooked components played a critical role in major life processes? We have now hints that zinc, as the divalent cation Zn 2+ and not monitored in the vast majority of growth media or biochemical assays, is integrating major metabolic features via the coordination of translation with one‐carbon metabolism [Danchin et al 2020 and Fig. 1].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…What if one of the overlooked components played a critical role in major life processes? We have now hints that zinc, as the divalent cation Zn 2+ and not monitored in the vast majority of growth media or biochemical assays, is integrating major metabolic features via the coordination of translation with one‐carbon metabolism [Danchin et al 2020 and Fig. 1].…”
Section: Figmentioning
confidence: 99%
“…In a surprising turn of things, the intricate coupling between one‐carbon metabolism and translation – initially witnessed as the omnipresent requirement for a methionine residue at the start of translated polypeptides – revealed that the connection was established via the homeostasis of Zn 2+ (Danchin et al 2020, and Fig. 1), mediated by the ribosomes as a main Zn 2+ store (Hensley et al , 2012).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this may not be the only cause if bacteria and archaea tRNAs are considered, as this modification is only present in tRNA Arg ACG. Most tRNA modifications are directly linked to the metabolic state through the requirement of key cofactor molecules, from which S-adenosylmethionine as chemical group donor and thiol source is the main paradigm ( Helm and Alfonzo, 2014 ; Danchin et al, 2020 ). However, adenosine deamination, Q/G transglycosylation (in eukaryotes) and pseudouridylation (that also involves a transglycosylation mechanism) ( Veerareddygari et al, 2016 ) are not directly related to the metabolic state of the cell.…”
Section: Possible Clues For the Absence Of Trna Genesmentioning
confidence: 99%
“…Within the scope of this review, we would like to emphasize that the enzymes involved in a large number of post-transcriptional modifications of tRNA (methylation, thiolation and incorporation of amino acid derivatives, dihydrouridine synthase, among others) require cofactors that constitute key molecules in metabolic pathways. Within them, it is worth mentioning S-adenosylmethionine (AdoMet), folate and NADPH (see Figure 1 ) ( Helm and Alfonzo, 2014 ; Danchin et al, 2020 ).…”
Section: Possible Clues For the Absence Of Trna Genesmentioning
confidence: 99%